Sabkha Ecosystems Volume V: The Americas - Khan, M. Ajmal; Boër, Benno; Ȫzturk, Münir; Clüsener-Godt, Miguel; Gul, Bilquees; Breckle, Siegmar-W (Tasks for Vegetation Science, 2016)
This book is a part of the Sabkha Ecosystems series which was designed to provide information on sabkha ecosystems of different regions and to add to the collective knowledge available about saline ecosystems. The comprehensive coverage assists the reader gaining a thorough understanding of sabkha geology, hydrology, geomorphology, zoology, botany, ecology and ecosystem functioning, as well as sabkha conservation, utilization and development. Volume I focused on The Arabian Peninsula and Adjacent Countries, volume II was based on describing saline ecosystems of West and Central Asia , volume III referred to Africa and Southern Europe, while volume IV focused on Cash Crop Halophyte and Biodiversity Conservation. The present volume V focuses on Americans. .